Implication of diethylcarbamazine induced morbidity and the role of cellular responses associated with bancroftian filariasis pathologies - Makunde, WH; Kamugisha, ML; Makunde, RA; Malecela-Lazaro, MN; Kitua, AY (Tanzania Journal of Health Research, 2006)
Pre and post-diethylcarbamazine treatment clinical expression, microfilaraemia prevalence and cellular responses were investigated in individuals in Tanga, Tanzania. Fifty-seven male individuals (aged =15 years old) were identified for further studies on IL-4, IL-6, IL-8, IFN-γ, IL-β, TNF-α and nitric oxide in plasma and hydrocoele fluid. Microfilarial prevalence in the examined individuals was 12% with a geometric mean intensity (GMI) of 838 mff/ml in a community with a population of 1018 individuals. Microfilaraemic hydrocoele stage II and III were the most frequent pathologies observed with prevalence of 17.5% and 42.1%, respectively. All study individuals treated with diethylcarbamazine (DEC) standard dose of 6mg/kg experienced post-treatment adverse events. There was no direct relationship between elevated IL- 6 and the occurrence and severity of clinical adverse effects post-treatment. The findings from this study suggests that, blood elevated cytokine profile is not the main etiological factor in the inflammatory responses developing after treatment of bancroftian filariasis infections and pathology with DEC. Plasma levels of cellular (cytokines) responses during treatment revealed a proportion of symptomatic patients. Prior to treatment, patients with hydroecoele had high levels of IL-6 than those without the pathology. In conclusion these findings do not support the hypothesis that pro-inflammatory cytokines are directly responsible for adverse events to DEC chemotherapy in bancroftian filariasis infections and pathologies such as hydrocoele, lymphoedema and elephantiasis. Tanzania Health Research Bulletin Vol. 8(1) 2006: 11-16